Induced Pluripotent Stem Cells: A New Frontier for Stem Cells in Dentistry. (November 2015) - Hynes, K.; Menichanin, D.; Bright, R.; Ivanovski, S.; Hutmacher, D.W.; Gronthos, S.; Bartold, P.M.
Induced pluripotent stem cells (iPSCs) are the newest member of a growing list of stem cell populations that hold great potential for use in cell-based treatment approaches in the dental field. This review summarizes the dental tissues that have successfully been utilized to generate iPSC lines, as well as the potential uses of iPSCs for tissue regeneration in different dental applications. While iPSCs display great promise in a number of dental applications, there are safety concerns with these cells that need to be addressed before they can be used in clinical settings. This review outlines some of the apprehensions to the use of iPSCs clinically, and it details approaches that are being employed to ensure the safety and efficacy of these cells. One of the major approaches being investigated is the differentiation of iPSCs prior to use in patients. iPSCs have successfully been differentiated into a wide range of cells and tissue types. This review focuses on 2 differentiation approaches—the differentiation of iPSCs into mesenchymal stem cells and the differentiation of iPSCs into osteoprogenitor cells. Both these resulting populations of cells are particularly relevant to the dental field.